Abortion Practices in Nepal: What does Evidence Show? - Bhandari, TR; Dangal, G (Nepal Journal of Obstetrics and Gynaecology, 2015)
Twenty-five years have passed since the global community agreed in Nairobi to address the high maternal mortality by implementing the Safe Motherhood Initiative. However, every year around 22 million women seek unsafe abortion in developing countries. Globally, the unsafe abortion accounts for 13% maternal deaths. Out of the total aborted women, around five million women were admitted to hospitals as a result of unsafe abortion. Similarly, more than three million women suffer from severe complications from unsafe abortion every year. In 2002, responding to the public voices and high attribution of unsafe abortion on maternal mortality, Nepal granted legal access to safe abortion introducing safe abortion act. Women can seek abortion up to 12 weeks of gestation for any indication. However, sex selective pregnancy termination is prohibited in Nepal. This study aimed to assess the results of various studies on abortion practices in Nepal. Literature published in PubMed, Lancet, Medline, WHO and Google Scholar web pages from 1990 to 2014 were used to prepare this paper. From 2004 to 2014, more than half a million women sought safe abortion care in Nepal. Despite the considerable progress, unsafe abortion is still a major issue in Nepal as it has been estimated that it constitutes half of all abortions undertaken every year. Published literature further showed that still an unmet need of safe abortion services exists in Nepal. However, the overall awareness of legal abortion was found to be high among Nepalese women. We found negative attitude of most people towards women who sought abortion care. Similarly, a large number of unmarried women were found at risk for seeking abortion care due to socio-cultural norms, values and stigmas in Nepal.